2005
DOI: 10.1590/s0100-879x2005001100009
|View full text |Cite
|
Sign up to set email alerts
|

Use of blends of bioabsorbable poly(L-lactic acid)/poly(hydroxybutyrate- co-hydroxyvalerate) as surfaces for Vero cell culture

Abstract: Vero cells, a cell line established from the kidney of the African green monkey (Cercopithecus aethiops), were cultured in F-10 Ham medium supplemented with 10% fetal calf serum at 37°C on membranes of poly(L-lactic acid) (PLLA), poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) and their blends in different proportions (100/0, 60/40, 50/50, 40/60, and 0/100). The present study evaluated morphology of cells grown on different polymeric substrates after 24 h of culture by scanning electron microscopy. Cell adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
1
8
0
5
Order By: Relevance
“…Cells adopted a round morphology with thin and long microvilli (Fig. (A)) in the porous area of PLLA, whereas in the PLLA non‐porous areas the cells were flattened with filaments . Round morphology and filaments are indicative of spreading cells with their thin cytoplasmatic filaments.…”
Section: Biodegradable Polymer Blends: Miscibility Characteristics Anmentioning
confidence: 88%
See 1 more Smart Citation
“…Cells adopted a round morphology with thin and long microvilli (Fig. (A)) in the porous area of PLLA, whereas in the PLLA non‐porous areas the cells were flattened with filaments . Round morphology and filaments are indicative of spreading cells with their thin cytoplasmatic filaments.…”
Section: Biodegradable Polymer Blends: Miscibility Characteristics Anmentioning
confidence: 88%
“…Changes in Vero cell (kidney cell line derived from the African green monkey) morphology and cellular differentiation pattern were noted depending on blend proportions possibly due to factors such as polymer surface energy, roughness, rigidity and surface tension (Fig. ) . Cells growing on porous or non‐porous areas in PLLA had different morphologies.…”
Section: Biodegradable Polymer Blends: Miscibility Characteristics Anmentioning
confidence: 95%
“…We showed that Vero cells produce extracellular matrix rich in fibronectin and collagen when cultured on dense or porous PLLA membranes, PHBV scaffolds or PLLA/PHBV blends of different proportions [21,25]. This finding may explain the observation of a significant proliferation rate despite the initially slow cell adhesion to these scaffolds [25,52].…”
Section: Cell Growth and Proliferation On Bioresorbable Polymersmentioning
confidence: 99%
“…18 Previously, the sterilized blends (n ¼ 6) were placed in a 96-well plate (Corning, USA) with 100 lL of culture medium and incubated at 37 C for 24 h. After incubation, 2 Â 10 5 cells/mL in 100 lL DMEM medium supplemented with 10% FBS were added to the wells containing the membranes. The cells were cultured for 2 and 24 h to allow cell adhesion and to conduct direct cell cytotoxicity assays, respectively.…”
Section: Cell Adhesion and Cytotoxicity Assaysmentioning
confidence: 99%
“…The cells were cultured for 2 and 24 h to allow cell adhesion and to conduct direct cell cytotoxicity assays, respectively. After the cells were washed twice with 0.1M phosphate-buffered saline (PBS), pH 7.4, at 37 C and incubated with 100 lL DMEM medium, a MTT assay mixture [10 lL per well, containing 5mg/mL of 3-(4,5-dimethylthia zol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT), Sigma] was added to each well and incubated for 4 h at 37 C. After 4 h, 100 lL of dimethyl sulfoxide (DMSO, Sigma) and 25 lL of glycine/Sorensen buffered solution replaced the assay mixture in each well to dissolve the formazan crystals, according to Santos et al 18 Absorbance was quantified by a spectrophotometer at 540 nm, using a Bio-Rad Model 550 microplate reader (Bio-Rad Laboratories, Hercules, CA). MTT is a colorless tetrazolium salt that forms a dark compound when oxidized by mitochondria, which is detected by spectrophotometer.…”
Section: Cell Adhesion and Cytotoxicity Assaysmentioning
confidence: 99%